Sources of methane to an Arctic lake in Alaska: An isotopic investigation. Issue 4 (11th April 2017) - Lecher, Alanna L.; Chuang, Pei‐Chuan; Singleton, Michael; Paytan, Adina
Abstract: Sources of dissolved methane (CH4 ) at Toolik Lake, Alaska, include both diffusion from lake sediments and groundwater entering the lake from its perimeter. Here we use hydrogen and oxygen isotopes in water (H2 O), carbon and hydrogen isotopes in CH4, and carbon isotopes in dissolved inorganic carbon (DIC) to calculate the relative importance of lake sediment and groundwater discharge as sources of dissolved CH4 to Toolik Lake. We also resolve the relative importance of the source contribution spatially within the lake and determine the processes controlling CH4 concentrations in groundwater surrounding the lake. Our findings, from a mixing model based on isotopes in CH4, suggest that groundwater is a more important source of CH4 at the perimeter of the lake where the water‐to‐air flux is high. Additionally, we find on the local scale that high groundwater methane concentrations may be better linked to areas around the lake where rain is the dominant source of water to the active layer, indicating that changes in precipitation and active layer thaw depth will impact methane concentrations in the active layer and, ultimately, the groundwater associated flux to Toolik Lake. Key Points: Tundra groundwater is an important source of methane to areas of the lake where the water to air dissolved methane flux is also higher Isotope analyses suggest that bacteria methyl‐type fermentation is the major pathway of methane production in the active layer Changes in precipitation in the Arctic could induce changes in methane production in groundwater due to changes in saturated zone thickness Plain Language Summary: This project investigates the cycling of methane, a green house gas, at an Arctic Lake in Alaska. The study shows that increases in rain could cause an increase in the amount of methane transported to Arctic lakes.